BIBLIOMETRIC ANALYSIS OF SCIENTIFIC RESEARCH ON COVID-19 VACCINES (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
This article presents a comprehensive bibliometric analysis of the scientific literature on COVID-19 vaccines. Against the backdrop of the global health, social, and economic impacts of the pandemic, vaccines emerged as a crucial protective measure, leading to a surge in related scientific research. The analysis is based on 5,957 scientific documents indexed in the Web of Science database, evaluating publication productivity, citation counts, and international collaboration indicators. Using VOSviewer for visual mapping, key research themes such as vaccine technology comparisons, effectiveness monitoring, and vaccine hesitancy were identified. The study also examined the most active authors, countries, and research institutions in this field, highlighting the leading roles of the United States, the United Kingdom, and China in scientific output. Prominent contributions from top universities such as Harvard and Oxford during the pandemic were emphasized. Overall, the research provides an in-depth overview of the intensity of scientific activity on COVID-19 vaccines, the strength of global collaboration, and the dissemination dynamics of the knowledge generated.Keywords: Covid-19, vaccine, Web of Science, vaccine technologies C8, C81, C88